Peningkatkan Hasil Belajar Passing Bawah Bola Voli Melalui Pendekatan Bermain Boardball Pada Siswa Sekolah Dasar - Siswoyo Siswoyo (Jurnal Pendidikan Dasar, 2019)
This study aims to improve learning outcomes in learning Passing Under Volleyball Through Boardball Playing Approach In Class IV Students of SD N 1 Nampu, Karangrayung Subdistrict, Grobogan District, Semester I Academic Year 2018/2019. This research is Classroom Action Research. This study consisted of 2 cycles. Each cycle consists of planning, carrying out actions, observations, reflections. This research was carried out in SDN 1 Nampu, Karangrayung Subdistrict, Grobogan Regency with the fourth grade research subjects with a total of 23 students consisting of 11 men and 12 women. The research instruments used were learning implementation observation sheets, observation sheets of student learning motivation, observation sheets of student learning interest, student response questionnaires and practice tests. The data analysis technique was carried out descriptively and through the calculation of predetermined formulas. The results showed that the results of learning volleyball passing through the boardball playing approach had a positive impact, this was seen in the results of student mastery that exceeded the predetermined KKM of 70 in the first cycle the completeness of learning outcomes reached 78.26% or 18 students from 23 students while in the second cycle the completeness of learning outcomes reached 91.30% or 21 students from 23 students. This shows an increase in student learning outcomes by 13.04%. This learning has a positive effect, which can increase students' interest and learning motivation as indicated by the average answers of students who stated strongly agree 64.29% on the results of student interest questionnaires, and students answer strongly agree 59.29% on the results of student motivation questionnaires. Key words: learning outcomes, volleyball under-passing learning, and boardball approach